Analysis of Local Content Policy Implementation in Company NJH - Daniel Simanjuntak; Adirizal Nizar (IPTEK Journal of Proceedings Series, 2020)
Oil and gas companies, contractors and suppliers, under the regulation by the Ministry of Energy and Mineral Resources (EMR), must implement local content implementation in procuring materials and services for oil and gas activities. Company NJH, as one of Production Sharing Contractors, faces problems in the inefficiencies of implementing the local content policy. Three main problems became apparent: unrealistic roadmap implementation, unstandardized contractor performance, and NJH’s human reso urces constraints. Qualitative methodology through interview sessions is used to analyze the current situation within NJH to understand the underlying issues, identify alternative solutions and formulate business solution proposal. Fishbone analysis is used to find the root cause of the inefficiencies. PDCA cycle analysis is also used to formulate business process improvement. The formation of a market research team is recommended to help resolving the roadmap implementation inefficiencies. The goal is to analyze the current SKK Migas PTK 007 Revision 4’s (PTK 007) roadmap adoptability and formulate optimized roadmap to be more practical to contractors and suppliers. A guidance program to support contractor’s documentation format and standards combined with the hiring of local content experts are also recommended as business solution with a goal to expedite verification processes.